Respuesta :
[tex]\begin{equation*} \begin{cases} 2x+y-z=0 \\ x -y+z=6 \\ x +2y+z=3 \end{cases}\end{equation*}[/tex]
[tex]\begin{equation*} \begin{cases} 2x+y-z=0 \\ -x +y-z=-6 \\ -x -2y-z=-3 \end{cases}\end{equation*}[/tex]
Adding all 3 equations
[tex]-3z=-9\\z=3[/tex]
[tex]\begin{equation*} \begin{cases} 2x+y=3 \\ -x +y=-3 \\ -x -2y=0 \end{cases}\end{equation*}[/tex]
Let's Express y by x
[tex]\begin{equation*} \begin{cases} y=3-2x \\ -x +y=-3 \\ -x -2y=0 \end{cases}\end{equation*}[/tex]
Substitute y in the 2nd equation
[tex]x+3-2x=-3\\-3x=-6\\x=2[/tex]
Now find y
[tex]-2+y=-3\\y=-1[/tex]
Answer: C) x=2, y=-1, z=3
Hello from Russia and sorry for my bad english:^)